Growth and Challenges of E-commerce in Pakistan - Asghar, Muhammad Muzammil (Journal of Global Social Transformation, 2025)
The e-commerce has become a revolution in the Pakistani economy and has transformed the classical business system, customer habits, and market access. In the past twenty years, the activities of internet penetration, mobile phone networks, digital payment systems, and transportation systems have increased at a very fast rate accelerating growth in online trading in the country. The young population of Pakistan and the rising popularity of social media sites have also contributed to increasing demand of online shopping, digital stores, and service-oriented e-commerce methods. The sector is also experiencing major problems despite this development such as poor digital infrastructure, distrust of online business, cyber vulnerability, lax regulation, low financial inclusion, and logistical inefficiencies. This research paper is a critical appraisal of the development trend of online trading in Pakistan and finds the key challenges that have impeded the sustainable development of online trading. The research applies the mixed-method analysis to examine the secondary data, policy reports, industry reports, and empirical data to evaluate the market trends, consumer adoption, and structural limitations. The results underline the fact that e-commerce has great potential to lead to the economic growth, employment, and inclusion of financial services; however, in order to achieve success in the long-term, the strategic policy changes, development of infrastructure, and mechanisms of trust are necessary.